Association study of polymorphisms in LRP1, tau and 5-HTT genes and Alzheimer's disease in a sample of Colombian patients (2006)
Analysis of genetic susceptibility factors for Alzheimer's disease (AD) in populations with different genetic and environmental background may be useful to understand AD etiology. There are few genetic association studies of AD in Latin America. In the present work, we analyzed polymorphisms in 3 candidate genes; the LDL receptor related protein-1, the microtubule-associated protein Tau and the serotonin transporter genes in a sample of 106 Colombian AD patients and 97 control subjects. We did not find a significant allelic or genotypic association with any of the three polymorphisms analyzed using different statistical analysis, including a neural network model or different sample stratifications. To date, APOE polymorphisms are the only genetic risk factors identified for AD in the Colombian population. It may be factible that future combination of high-throughput genotyping platforms and multivariate analysis models may lead to the identification of other genetic susceptibility factors for AD in the Colombian population. © Springer-Verlag 2005.